Improving Strawberry Varieties by Somaclonal Variation - Cheol-Min Yoo; Cheryl Dalid; Catalina Moyer; Vance Whitaker; Seonghee Lee (EDIS)
Somaclonal variation is a breeding method utilizing natural genetic variation induced by a tissue culture process instead of by hybridization. This offers an alternative to mutation breeding for the introduction of new genetic variations in existing strawberry varieties. The main purpose of this new 5-page publication of the UF/IFAS Horticultural Sciences Department is to share the potential of this technique with plant breeders in the public and private industries. The secondary purpose is to educate the industry and the public on the scientific background of somaclonal variation. Written by Cheol-Min Yoo, Cheryl Dalid, Catalina Moyer, Vance Whitaker, and Seonghee Lee. https://edis.ifas.ufl.edu/hs1448